Analisis Swot Dalam Strategi Pengembangan Usaha D-Box Jakarta - Mujahidin, Ahmad Nuril; Nurlenawati, Netti; Triadinda, Dexi (Universitas Gorontalo, 2025)
The purpose of this research is to determine the appropriate strategy for the Jakarta D-Box business so that it can continue to grow and compete in the future. This study applies a quantitative descriptive method. Sampling in this study was non-probability sampling with a purposive sampling technique in which the total population is unknown. The decision on the number of samples is determined by the Lameshow formula. This study uses an analytical tool in the form of a SWOT analysis. Based on the results of the IFAS calculation, a total value of (+) 0.96 was obtained, then the EFAS calculation obtained a total value of (+) 1.25. So that D-Box Jakarta is in quadrant 1 which is a very favorable situation. This condition supports aggressive growth policies (growth oriented strategy). Therefore, to develop the D-Box Jakarta effort, an alternative SO strategy can be used, using strengths to take advantage of the opportunities it has. Follow-up research uses the Business Model Canvas (BMC) to provide convenience to D-Box Jakarta business owners in understanding the business model being run